Lumbar muscle stiffness is different in individuals with low back pain than asymptomatic controls and is associated with pain and disability, but not common physical examination findings. (February 2020) - Koppenhaver, Shane; Gaffney, Emily; Oates, Amber; Eberle, Laura; Young, Brian; Hebert, Jeffrey; Proulx, Laurel; Shinohara, Minoru
Abstract: Background: Lumbar muscle dysfunction is commonly implicated in low back pain (LBP). Shear-wave elastography (SWE) uses ultrasound technology to quantify absolute soft tissue stiffness (shear modulus), thereby allowing for estimation of individual muscle contraction and function. Objectives: To compare resting and contracted stiffness of lumbar spine musculature in individuals with and without LBP using SWE. A secondary aim was to explore for relationships between common self-report and physical examination measures and resting and contracted muscle stiffness in individuals with LBP. Design: Cross-sectional. Methods: Shear modulus of the lumbar musculature was measured in 60 participants with LBP and 60 asymptomatic controls (120 total) using SWE. The lumbar erector spinae were imaged at rest only, while the lumbar multifidus was imaged at rest and during contraction. Before imaging, participants with LBP underwent a standardized clinical examination including a brief history, self-report questionnaires, and a physical examination. Lumbar muscle shear modulus was compared between participants with LBP and asymptomatic controls using ANCOVA. Potential associations between shear modulus and selected self-report and physical examination measures were assessed using correlation analysis. Results: Stiffness of the erector spinae and lumbar multifidus at rest (but not during contraction) was greater in participants with LBP than in asymptomatic controls ( p  < 0.05). Many of the self-report measures, but none of the physical examination findings were associated with muscle stiffness. Conclusion: Resting lumbar muscle stiffness is greater in individuals with LBP than asymptomatic controls and is associated with self-reported pain and disability, but not physical exam findings. Highlights: Stiffness of the lumbar musculature was measured using shear-wave elastography. Resting muscle stiffness was greater in participants with LBP than in controls. Contracted muscle stiffness was not different in participants with LBP than controls. Resting muscle stiffness was associated with self-reported pain and disability. Lumbar muscle stiffness was not associated with physical exam findings.